Micron to Nano Au Particles Incorporation in Different Stages of Pyrite, in Bau, Sarawak, Malaysia - Sundarrajan, Vijay Anand; Marjon, Carolin Nicole; Musta, Baba (Indonesian Journal on Geoscience, 2025)
In eastern Malaysia, Bau is the significant sediment hosted gold deposit (SHG), and Sarawak Province was the main gold (Au) producer in East Malaysia. The annual production rate was approximately 40 ̶ 50 metric tons of Au (high grade). The Bau mining is located 40 km SW of Kuching City, Sarawak. For the present study, around twenty-five samples were collected in the Au mineralized zones of Bau areas. The polished thin sections were prepared for mineral chemistry and fluid petrography analyses. The samples were studied through transmission microscope, Electron Probe Micro-Analyzer (EPMA), and fluid inclusion studies. From ore petrography, four stages of pyrite were classified. The first generation of pyrite is the early stage of diagenetic pyrite (Py1), Py2 is subeuhedral pyrite, Py3 is zoned pyrite, and Py4 is post-diagenetic pyrite. The mineral chemistry of different stages of pyrite was measured through EPMA. However, it is worth noting that the concentrations of these trace elements in pyrite have decreased pre-diagenetic and post diagenetic stages. The precipitation of Au in the main stages of pyrite was mainly controlled by pyrite structure, fluid ligands, and the temperature of crystallization.